Beyond death and graft survival—Variation in outcomes after kidney transplantation. Results from the NSQIP Transplant beta phase. Issue 9 (21st May 2019) - Parekh, Justin R.; Hirose, Ryutaro; Foley, David P.; Grieco, Arielle; Cohen, Mark E.; Hall, Bruce L.; Ko, Clifford Y.; Greenstein, Stuart
Abstract : The National Surgical Quality Program (NSQIP) Transplant was designed by transplant surgeons from the ground up to track posttransplant outcomes beyond basic recipient and graft survival. After an initial pilot phase, the program has expanded to 29 participating sites and enrolled more than 4300 recipient‐donor pairs into the database, including 2876 complete kidney transplant cases. In this analysis, surgical site infection (SSI), urinary tract infection (UTI), and reoperation/intervention were evaluated for kidney transplant recipients. We observed impressive variation in the crude incidence between sites for SSI (0%‐17%), UTI (0%‐14%), and reoperation/intervention (0%‐25%). After adjustment for donor and recipient factors, 2 sites were outliers with respect to their incidence of UTI. For the first time, the field of transplantation has data that demonstrate variation in kidney recipient surgical outcomes between sites. More importantly, NSQIP Transplant provides a powerful platform to improve care beyond basic patient and graft survival. Abstract : The authors present preliminary findings from NSQIP Transplant, highlighting variation in surgical outcomes after kidney transplant across centers.